Biotic condition assessment and the implication for lake fish conservation: a case study of Lake Qionghai, China - Yong Liu; Zhou, Feng; Guo, Huaicheng; Yu, Yajun; Zou, Yufei (WATER AND ENVIRONMENT JOURNAL, 2009)
Conserving fish in lakes requires the systematic analysis and assessment of fish species. The issues, conservation needs and fish assemblage changes are described for Lake Qionghai (China). The annual fishery production (AFP) was analysed from 1949 to 2003, which indicated a high disturbance of the aquatic ecosystem in Lake Qionghai caused especially by fisheries. The continuous increase in AFP and the introduction of economically important fish species have changed the fish species structure and diversity of the lake. Only five of 20 native fish species remained extant in 2003. The alien species accounted for 83.58% of the total fish production in 2003. Scoring criteria for 10 indexes of biotic integrity (IBI metrics) were selected for Lake Qionghai. The overall IBI score decreased from 40 in the 1940s to 26 in the 1980s to 20 in 2003. Changes in biotic condition were mainly caused by the destruction of fish physical habitat, pollution, bycatch and the invasion of alien species. Based on the IBI analysis, an ecosystem approach was developed for fish conservation in Lake Qionghai, including conservation at the watershed scale, habitat improvement and restoration, rebuilding of aquatic ecosystems and adaptive ecosystem-based fishery management.